Image Watermarking Scheme for CT and MRI Scan Images with DWT and SVD Transforms - Rajyalakshmi, V; Ramesh, K (International Journal of Computer Sciences and Engineering, 2025)
Watermarking is the process of hiding digital information in a cover image; the hidden information should, but does not need to, contain a relation to the cover image. The digital watermarking is a field of information hiding which hide the crucial information in the original data for protection illegal duplication and distribution of multimedia data. The discrete wavelet transform (DWT) is an implementation of the wavelet transform using a discrete set of the wavelet scales and translations obeying some defined rules. In this paper we are analyzing about different techniques like DWT, singular value decomposition (SVD) and combination of both with a scaling factor. Apart from all the cases prospective method will gives better output. In the prospective method for the cover image we are implementing SVD to LL band and altering the diagonal singular value coefficients with watermark image by using a scaling factor. The performance of this technique shows improvement in output, peak signal to noise ratio (PSNR) and mean square error (MSE).